Ti6554 titanium alloy electrically assisted compression: modelling and simulation based on dislocation density theory. Issue 1 (1st December 2022) - Zhou, Y; Wu, C; Qu, Z; Lin, B
Abstract : Electrically assisted compression experiments were conducted on Ti6554 titanium alloy to investigate the electroplasticity behavior under different process parameters (current density, duty cycle) and to analyze the effect of pulsed current on flow stress and temperature. An electroplasticity constitutive model based on dislocation density theory was developed and using ABAQUS subroutine secondary development for electrically assisted compression simulation. The results show that the established electroplasticity constitutive model can better predict the true stress-strain curves under different process parameters, and the average error is controlled at 6%. The evolution law of dislocation density reveals that α, which characterizes the dislocation strength, is smaller with the increase of current density, n and K2, which characterize the dynamic recovery mechanism of the material, increase with the increase of current density, and the dislocation density ρ decreases with the increase of deformation temperature.